Transmission dynamics of ESBL/AmpC and carbapenemase-producing Enterobacterales between companion animals and humans - Menezes, Juliana; Frosini, Siân-Marie; Weese, Scott; Perreten, Vincent; Schwarz, Stefan; Amaral, Andreia J.; Loeffler, Anette; Pomba, Constança (Frontiers in Microbiology, 2024)
Antimicrobial resistance mediated by extended-spectrum beta-lactamase (ESBL)- and plasmid-mediated cephalosporinase (AmpC)-producing Enterobacterales, as well as carbapenemase-producing Enterobacterales have globally increased among companion animals, posing a potential health risk to humans in contact with them. This prospective longitudinal study investigates the transfer of ESBL/AmpC- and carbapenemase-producing Enterobacterales between companion animals and their cohabitant humans in Portugal (PT) and the United Kingdom (UK) during animal infection. Fecal samples and nasal swabs collected from dogs and cats with urinary tract infection (UTI) or skin and soft tissue infection (SSTI), and their cohabitant humans were screened for resistant strains. Relatedness between animal and human strains was established by whole-genome sequencing (WGS). ESBL/AmpC-producing Enterobacterales were detected in companion animals (PT=55.8%; UK=36.4%) and humans (PT=35.9%; UK=12.5%). Carbapenemase-producing Enterobacterales carriage was observed in one dog from Portugal (2.6%) and another dog from the UK (4.5%). Transmission of index clinical ESBL-producing Escherichia coli and Klebsiella pneumoniae strains to cohabitant humans was observed in three Portuguese households (6.9%, n=43), with repeated isolation of the index strains on fecal samples from the animals and their cohabiting humans. Additionally, longitudinal sharing of E. coli strains carried by companion animals and their owners was observed in other two Portuguese households and two households from the UK. Furthermore, a multidrug-resistant ACT-24-producing Enterobacter hormaechei subsp. hoffmannii strains were also shared within another Portuguese household. These results highlight the importance of the household as an epidemiological unit in the efforts to mitigate the spread of antimicrobial resistance, further emphasizing the need for antimicrobial surveillance in this context, capable of producing data that can inform and evaluate public health actions.